Konsistensi Struktur Argument by Commitment dalam Editorial Harian Bisnis Indonesia: Perspektif Douglas Walton - Pilipus Wai Lawet; Yuliana Setyaningsih (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
Consistency is very essential in writing editorial rubrics because it shows commitments of the author and his institution. Author and media institution who have high commitments in writing editorial argumentation can increase the level of readers' confidence toward the content of editorials. This research is intended to optimize the consistency of the construction of argument by commitment in Bisnis Indonesia editorials. Data collection methods used were documentation and interview methods. The research data were in the form of editorial texts containing arguments. The data analysis method used was the qualitative data analysis. Besides, the content analysis method was also applied. The research result showed that there were inconsistencies of arguments by commitment used in the editorials. The inconsistencies occured because a deep understanding of the concept of argument by commitment in writing editorials has not been understood well by editorial writers. Therefore, the steps of optimizing the consistency of argument by commitment must be done as follows: (1) understanding the concept of argument by commitment, (2) designing an argument by commitment scheme, and (3) asking critical questions.